Environmental factors and their recognition in the cost structure in the fabrication of burial vaults: A case study. Municipality of Palavecino, Venezuela (Ágora de Heterodoxias, 2016)
The paper is about a study of case that identifies the environmental factors that are affected by the burial vaults manufacturing process in cemeteries managed by private companies located in the Municipality of Palavecino, Lara State, Venezuela.  Due to the nature of the production of vaults, it inevitable generates negative impacts on the environment because the implementation of these activities is developed on extensive grounds. These companies must recognize the damage that they generate and evaluate those damages in order to implement measures to reverse the negative impacts.  The study includes analysis from the following dimensions: a) Effects on the environment, b) Identification of environmental costs, c) Recognition in the cost structure. The case analysis includes two companies that manage private cemeteries: Metropolitan Park East Cemetery and Heavenly Gardens. semi-structured interviews were made to the key informants in addition to the direct observation on the site. The results showed that the factors that suffer environmental degradation are: water, soil, air, flora and ecosystem, and the manufacturing processes that generate these negative consequences were: deforestation, land preparation and construction vaults. The design of costs structure presents environmental costs and total costs of a disaggregated form and it reveals that companies apply mitigation measures as reforestation and replanting of trees, to try to reverse the environmental damage that its model of exploitation produces.
Keywords: environmental impacts, environmental costs; manufacturing vaults; cemeteries; cost structure